Determinant Corporate Social Responsibility Disclosure, Size of Companies Registered of Bursa Efek Indonesian Property nd Real Estate - Ravi, Muhammad; Mulya, Hadri (Devotion : Journal of Research and Community Service, 2022)
This study discusses how Profitability and Leverage on Corporate Social Responsibility Disclosures are moderated by company size. This study uses secondary data as a data source with a total sample of 135 companies listed on the property and real estate sector stock exchanges with a time span from 2016 to 2020. The results of this study indicate that the Profitability variable does not have a significant effect on Corporate Social Responsibility Disclosure has a significant effect if it is moderated by Size Companies while the Leverage variable has a significant effect on Corporate Social Responsibility Disclosure but does not have a significant effect if it is moderated by Size Companies.